Surface waves at an interface of two metamaterial structures with interelement coupling - Radkovskaya, A; Tatartschuk, E; Sydoruk, O; Shamonina, E; Stevens, C; Edwards, D; Solymar, L (2010)
A configuration of two strongly coupled homogeneous two-dimensional metamaterial lattices of resonant elements is shown to be able to propagate surface magnetoinductive waves along the interface by virtue of coupling between the elements at the boundary. A study of the dispersion equations reveals the existence of two separate pass bands for surface waves which may partly overlap with pass bands supporting bulk waves. Experiments are reported on a structure consisting of 90 magnetically coupled capacitively loaded resonant rings designed to operate around 55 MHz. The measured current distributions and dispersion curves extracted from the experimental data are compared both with numerical simulations, using the generalized Kirchhoff's equation and with analytical expressions derived on the assumption of nearest-neighbor interaction. Excellent agreement between the three approaches is found. Considering that surface waves of various kinds have found a wide range of applications in the past, it is envisaged that this surface wave will open up fresh possibilities. A number of examples are presented. It is conjectured that other existing metamaterial structures might also be suitable candidates for propagating analogous surface waves. © 2010 The American Physical Society.